Comparative Study of Immediate and Delayed Lateral Ridge Expansion Technique in the Atrophic Posterior Mandibular Ridge (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: ridge expansion; alveolar ridge split; crestal bone loss